2-Abstracts Conférences JRANF 2024_JAIM 2024_16.3 - MOIFO Boniface; ADAMBOUNOU Kokou; SONHAYE Lantam; GNAOULE Debato Tina; KOUANDONGUI BANGUE SONGROU Francky; Guida Seidou; Ibrahima Niang; TOURE Abdoulaye; ADJADOHOUN Sonia; NEOSSI GUENA Mathurin; et al. (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2024)
2-Abstracts Conférences JRANF 2024_JAIM 2024_16.3